DNA Methylation Sustains “Inflamed” Memory of Peripheral Immune Cells Aggravating Kidney Inflammatory Response in Chronic Kidney Disease - Chen, Xiao-Jun; Zhang, Hong; Yang, Fei; Liu, Yu; Chen, Guochun (Frontiers in Physiology, 2021)
The incidence of chronic kidney disease (CKD) has rapidly increased in the past decades. A progressive loss of kidney function characterizes a part of CKD even with intensive supportive treatment. Irrespective of its etiology, CKD progression is generally accompanied with the development of chronic kidney inflammation that is pathologically featured by the low-grade but chronic activation of recruited immune cells. Cumulative evidence support that aberrant DNA methylation pattern of diverse peripheral immune cells, including T cells and monocytes, is closely associated with CKD development in many chronic disease settings. The change of DNA methylation profile can sustain for a long time and affect the future genes expression in the circulating immune cells even after they migrate from the circulation into the involved kidney. It is of clinical interest to reveal the underlying mechanism of how altered DNA methylation regulates the intensity and the time length of the inflammatory response in the recruited effector cells. We and others recently demonstrated that altered DNA methylation occurs in peripheral immune cells and profoundly contributes to CKD development in systemic chronic diseases, such as diabetes and hypertension. This review will summarize the current findings about the influence of aberrant DNA methylation on circulating immune cells and how it potentially determines the outcome of CKD.